Enhanced Ionic/Electronic Transport in Nano‐TiO2/Sheared CNT Composite Electrode for Na+ Insertion‐based Hybrid Ion‐Capacitors. (18th November 2019) - Luo, Sainan; Yuan, Tao; Soule, Luke; Ruan, Jiafeng; Zhao, Yahui; Sun, Dalin; Yang, Junhe; Liu, Meilin; Zheng, Shiyou
Abstract: Ion‐insertion capacitors show promise to bridge the gap between supercapacitors of high power densities and batteries of high energy densities. While research efforts have primarily focused on Li + ‐based capacitors (LICs), Na + ‐based capacitors (SICs) are theoretically cheaper and more sustainable. Owing to the larger size of Na + compared to Li +, finding high‐rate anode materials for SICs has been challenging. Herein, an SIC anode architecture is reported consisting of TiO2 nanoparticles anchored on a sheared‐carbon nanotubes backbone (TiO2 /SCNT). The SCNT architecture provides advantages over other carbon architectures commonly used, such as reduced graphene oxide and CNT. In a half‐cell, the TiO2 /SCNT electrode shows a capacity of 267 mAh g −1 at a 1 C charge/discharge rate and a capacity of 136 mAh g −1 at 10 C while maintaining 87% of initial capacity over 1000 cycles. When combined with activated carbon (AC) in a full cell, an energy density and power density of 54.9 Wh kg −1 and 1410 W kg −1, respectively, are achieved while retaining a 90% capacity retention over 5000 cycles. The favorable rate capability, energy and power density, and durability of the electrode is attributed to the enhanced electronic and Na + conductivity of the TiO2 /SCNT architecture. Abstract : This work presents a high‐performance 3D TiO2 /sheared‐carbon nanotube (SCNT) anodic material for Na + ‐based capacitors (SICs) using a framework that combines the benefits of reduced graphene oxide and CNTs to enable high rate capability and stability. The TiO2 /SCNT composite anode is used in a SIC and exhibits gravimetric and volumetric power densities of 54.9 Wh kg –1 and 1410 W kg –1, respectively.